A educação inclusiva em uma escola da rede municipal de Manaus: desafios e percepções na sala de aula - Morais, Ana Stela da Silva (Brasil, 2023)
The proposal of Inclusive Education has aroused the interest of the whole society for being an effective form of social inclusion in the Federal Constitution (1988), with regard to Education, it provides for general rules such as access to school for all citizens, the schooling for people with special needs, the use of the mother tongue, guaranteed rights, State attributions, financial resources and training of education professionals. The Salamanca Declaration (1994) advocates equal opportunities for people with special needs, and also calls on volunteers and families to engage in this task. With this document, the Educational Systems of Governments began to organize themselves in a perspective where the conditions of access and permanence of Deaf subjects are guaranteed. Special Education is also addressed through Law no. 9.394/96, within it, education is everyone's right without distinction. From Law nº 10.436/02, which officially recognizes the Brazilian Sign Language - Libras, regulated by Decree nº 5.626/05, they were fundamental, mainly, because they provided for the inclusion of the discipline of Libras in the curricula of undergraduate courses. We also emphasize the importance of the relationship between teacher/student for success in learning, calling the attention of education systems to the need for a comprehensive view of the curriculum, with a view to eliminating the barriers that hinder or prevent the participation and learning of Deaf students in regular schools. In this sense, the general objective of the work was to verify the main difficulties in the process of inclusion of the Deaf student. In order to carry out this work, a qualitative and bibliographical research was chosen. The results found were the need for more public policies for the education and training of professionals, guaranteeing quality education for this specific public, with a lot of struggle from those engaged in defending a more just and caring Brazil in the issues of Deaf students. Therefore, this study, one can see the complexity and scope of the theme, impossible to exhaust it in the dimensions of this text.